Biomedical laboratory scientist students as supervisors for nursing students in venous blood sampling - Helene Margrethe Storebø Opheim; May-Tove Furuseth; Kristin Isabella Kirkengen Espe; Bjarne Hjeltnes; Elisabeth Hessevaagbakke (Bioingeniøren, 2021)
The focus of the article is what Biomedical Laboratory Scientist students experience and emphasize as fellow student supervisors in venous blood sampling for nursing students.